Manajemen Persediaan Obat di Rumah Sakit Primer: Peran EOQ dalam Efisiensi Biaya Penyimpanan (Studi Kasus) - Aris Kurniawan; Intantyana Asri, Fusarina Mumpuni; Chalidyanto, Djazuly; Prayitno, Antonius Adji (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research investigates the application of the Economic Order Quantity (EOQ) method to improve drug inventory management in a primary hospital pharmacy, with a particular focus on reducing storage costs. A descriptive quantitative approach was applied using secondary data from January to December 2024, covering annual demand, purchase price, ordering cost, and holding cost. The analysis concentrated on fast-moving vital essential and moderate vital drugs that are critical for sustaining patient treatment. The study revealed inefficiencies in the hospital's procurement practices, with some medicines simultaneously facing overstock and stockout risks, indicating weak planning. EOQ calculations provided alternative procurement quantities that were smaller but more frequent, resulting in lower storage costs and better stock control. Simulation outcomes demonstrated notable cost savings, particularly for Flamicort, Diazepam, and Ventolin. These findings emphasize the value of integrating EOQ into hospital pharmaceutical logistics to reduce financial losses, strengthen supply chain efficiency, and ensure the continuous availability of essential medicines in primary hospital settings.